Academic Medical Libraries and Accessibility Challenges The Conformance of the Websites with the WCAG2 1 - Zare, Soheila; Rahmatizadeh, Shahabedin; Valizadeh-Haghi, Saeideh (DESIDOC Journal of Library & Information Technology, 2021)
Website accessibility is a key factor in meeting individuals’ needs and expectations. Considering the lack of research on the accessibility of Iranian medical libraries’ websites, the aim of the present study is to evaluate the compliance of the central library websites of Iranian universities of medical sciences using the latest WCAG2.1 guideline. The research includes all the 51 homepages of the central libraries of Iranian medical universities. The accessibility evaluation of each homepage performed using “Webaccessibility” automated testing tool. The Kruskal–Wallis one-way analysis of variance was performed to explore the association of the compliance score of libraries’ websites among the three categories of medical universities. The findings of the present study revealed that none of the central library websites of the Iranian medical sciences universities are fully compliant with WCAG2.1, and the mean compliance score of accessibility was 77.26 ± 5.862 percent. The low accessibility of the library websites may result in making online information services and resources inaccessible and unusable to users who are disabled. Therefore, it is necessary for library managers and website designers to solve the accessibility problems and improve the accessibility of the websites to make them accessible for all users.